Applicabillity of teaching techniques fot the first pedagogical stage in a class of english as a second languaje for students of fourth level at Antonio Ríos Saavedra Elementary School, Boquerón - Chiriquí, 2013 - Saldaña, Darling (UDELAS, 2013)
This project intends to provide practical teaching techniques to be used at the three pedagogical stages in an english class, which it perfoms on its best anda the viable way, including relevant details such as the activities and resources, pertinent within a class.